Calculation of head difference at two sides of a cut-off barrier during excavation dewatering. (November 2017) - Shen, Shui-Long; Wu, Yong-Xia; Misra, Anil
Highlights: Head difference is calculated inside/outside an enclosed excavation due to dewatering. Two parts of head difference: (i) below the barrier, (ii) convergence into opening. Head difference below barrier can be derived from hydraulic analyses. Head difference by convergence into opening obtained from numerical analyses. Proposed calculation approach was verified from a field measured case. Abstract: This paper proposed a series of simple equations to calculate the head difference at the two sides of waterproof curtain. The barrier effect of waterproof curtain is considered from two situations with respect to without barrier case: (i) groundwater head difference below the barrier and (ii) groundwater head difference by convergence into the opening. The solution for the first situation can be derived from hydraulic analyses and the second situation can be obtained using a numerical analysis. The final groundwater head difference is the sum of these two situation according to the superposition principal. In the proposed equations, the head difference is expressed as a function of the inserted depth of the barrier into confined aquifer, the ratio of the hydraulic conductivity of the aquifer, the thickness of the aquifer, and hydraulic gradient under normal conditions. Finally, the proposed equation was applied to a field case to verify the validity of the proposed approach. Compared with the field data, the results show that the proposed method is reasonable.